78.9k views
1 vote
Find the value of the expression.

5 ( 2² - 1 ) + 33 / 5 x 3 - 12

2 Answers

3 votes

5 ( 2² - 1 ) + 33 / 5 x 3 - 12

= 5 ( 4 - 1 ) + 6.6 x 3 - 12

= 5 (3) + 19.8 - 12

= 15 + 19.8 - 12

= 22.8

User Doliveras
by
5.4k points
1 vote

Remember to follow PEMDAS, and the rule of left to right.

2^2 = 4

4 - 1 = 3

5(3) + 33/5 x 3 - 12

5 x 3 = 15

33/5 = 6.6

6.6 x 3 = 19.8

15 + 19.8 - 12 = 22.8

22.8 is your answer

hope this helps

User Ranjith King
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.